Practice and presence: a gathering for Christians in health care - finding God in all things - Daniel W. OߣNeill (Health for All Nations, 2017)
This conference report describes the content of the Practice and Presence confereence at Duke Divinity School in May 2017, and the approach to Ignatian practices of reflection, prayer and discernment applied to the practice of medicine, along with its application in global health contexts.